GMJ 2019
DOI: 10.31661/gmj.v8i0.1520
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Two-dimensional Gel Electrophoresis Maps for Amastigote-like Proteomes of Iranian Leishmania Tropica and Leishmania major Isolates

Abstract: Background: Leishmania major and Leishmania tropica are the main causative agents of cutaneous leishmaniasis. Proteomics as a novel approaches could be used to evaluate protein expression levels in different stages of Leishmania species. We compare the protein contents of amastigote-like forms in L. tropica and L. major using two-dimensional gel electrophoresis (2-DE) and bioinformatics methods. Materials and Methods: Leishmania parasites were isolated from the lesions of Iranian patients and identified using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It was concluded that the levels of protein expression in the amastigote form of L. tropica and L. major strains were distinct. It was found that the use of proteomics tools, statistical analysis of Leishmania’s proteome in Iranian isolates, and comparison of their protein expression levels could aid researchers in developing a more accurate diagnosis and treatment for the disease [ 65 ].…”
Section: Proteomic Analysis Of Different Leishmania Speciesmentioning
confidence: 99%
“…It was concluded that the levels of protein expression in the amastigote form of L. tropica and L. major strains were distinct. It was found that the use of proteomics tools, statistical analysis of Leishmania’s proteome in Iranian isolates, and comparison of their protein expression levels could aid researchers in developing a more accurate diagnosis and treatment for the disease [ 65 ].…”
Section: Proteomic Analysis Of Different Leishmania Speciesmentioning
confidence: 99%
“…In the field of the molecular differences between procyclic, metacyclic and amastigote forms, several investigation was reported the proteome of promastigotes and amastigotes forms of L. major , L. infantum , L. donovani and L. Mexicana . Most of these reports have used 2DE map to detect global differences of Leishmania species life stages (Amiri-Dashatan et al 2020b ; Ashrafmansouri et al 2019 ), which may be due to post-translational modifications (PTMs) affect charged amino acids (Rosenzweig et al 2008 ). Therefore, gel free approaches provide a valuable resource to higher proteome coverage and more precise quantitative information.…”
Section: Introductionmentioning
confidence: 99%
“…infantum, L. donovani and L. Mexicana. Most of these investigations used 2DE map to detect global differences of different life stages of different species [14], which may be due to post-translational modifications (PTMs) affect charged amino acids [15].Therefore, gel free approaches provide a significant resource to higher proteome coverage and more precise quantitative information. SWATH is a recently developed label free quantitative method, in which data independent acquisition is coupled with peptide spectral library match [16,17].…”
Section: Introductionmentioning
confidence: 99%